P110: Relapse in patients managed in the emergency department for acute asthma: a systematic review. (2nd June 2016) - Rowe, B.H.; Hill, J.; Arrotta, N.; Villa-Roel, C.; Dennett, E.
Abstract : Introduction: Despite the provision of evidence-based care, approximately 15% of patients discharged from the emergency department (ED) after being treated for asthma exacerbations will relapse within two weeks. This study summarizes the evidence regarding relapses and factors associated with increased relapse in patients discharged from EDs after being treated for asthma exacerbations.Methods: Comprehensive literature searches were conducted in seven electronic databases; manual and grey literature searches were performed. Studies tracking outcomes for adults after ED management and discharge were included. Methodological quality was assessed using the Newcastle-Ottawa Scale (NOS) and the Risk of Bias (RoB) tools. Studies were summarized using medians and interquartile ranges (IQR) or mean and standard deviation (±SD), as appropriate.Results: From 793 potentially relevant citations, 178 articles underwent full text review and 10 studies involving 32, 923 patients were included. The majority of the studies were of high quality according to NOS and RoB tools. Relapse proportions were 8±3%, 12±4%, and 14±6% at one, two, and four weeks, respectively. Female sex was the most common statistically significant reported factor associated with an increased risk of relapse within 4 weeks of ED discharge for acute asthma. Other factors significantly associated with relapse were past healthcare utilization and symptom duration.Conclusion: After ED management and discharge of acute asthma, a considerable proportion of patients will relapse within the first four weeks. Factors such as female sex, past healthcare utilization, and symptom duration were commonly and significantly associated with relapse occurrence. Identifying patients with these features could provide guidance to clinicians during the ED-discharge decision-making.